Assessment of Barriers and Challenges to the Screening and Linkages of Non-Communicable Diseases by Community Health Volunteers in Nyeri County, Kenya - Mugambi, Kenneth; Nyaberi, Jackline; Echoka, Elizabeth (Global Journal of Health Sciences, 2024)
Purpose: Non-communicable diseases (NCDs) are a significant global health challenge, contributing to 50% of worldwide morbidity and 63% of mortality. The burden is particularly substantial in low"”and middle-income countries (LMICs), where 80% of NCD-related deaths occur. This study evaluated barriers and challenges to effective screening and linkages of NCDs in Nyeri County. Methodology: A quasi-experimental non-equivalent pre-and post-test design was conducted from May 2022 to March 2023. The study employed multistage cluster and random sampling to select ten community units, resulting in 150 community health volunteers (CHVs) in the control unit and 150 in the intervention group. Data collection was facilitated through the KOBO app. Qualitative data involved six homogeneous focus group discussions (FGDs) and ten key informant interviews (KIIs), audio-recorded, transcribed, and analyzed using N-Vivo 12. Findings: Limited awareness, inadequate healthcare infrastructure, cultural beliefs, financial constraints, fragmented healthcare systems, and challenges linking individuals to appropriate care services. The article explores strategies to overcome these barriers, emphasizing the importance of collaborative approaches involving stakeholders at various levels. Unique Contribution to Theory, Practice and Policy: Raising awareness about NCDs and preventive measures is crucial and can be achieved through targeted health education campaigns and community outreach programs. Addressing healthcare infrastructure deficiencies, Cultural beliefs and practices and engaging with local communities and incorporating cultural sensitivity into healthcare delivery can help bridge the gap between traditional beliefs and modern healthcare practices. Financial constraints pose a significant barrier particularly in LMICs, therefore innovative financing mechanisms, e.g. health insurance schemes can help alleviate this burden. Finally, strengthening linkages between screening programs and care services is critical for the timely diagnosis and management of NCDs and this requires establishing robust referral systems and ensuring continuity of care for patients throughout their healthcare journey. Addressing the multifaceted barriers to NCD screening and care linkage is essential for improving health outcomes through implementing targeted community intervention like NCD wheel and a user-friendly interface mobile app that contains messages and info about NCDs barriers to care and facilitators to good NCD care and treatment. This will be positively reinforced by a stronger collaboration among stakeholders and community.